(untitled) (Universal International Scientific Journal, 2026)
After World War II, significant changes occurred in the population of the republic: the number of children and the working-age population decreased, and the number of elderly people increased. The main reason for this is the decrease in birth rates and high mortality rates as a result of the hardships of the war years. In the pre-war years, the difference between men and women was such that there were more men. This article discusses the issues of employment of workers and employees in the Samarkand region.